О чем плачут лошади: рассказы / Федор Абрамов ; предисловие А. Акимова - Абрамов Федор Александрович (Школьная библиотека, 2011)
Экземпляры: ф11 (20120413) / Инвентарный номер: 47453 / Цена: 183.38 / Сис.шифр: Р2ср / Авт.знак: А 16 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6